(untitled) (Medico Legal Update, 2021)
The aims of this study to find the link between each of the parasites(E. histolytic and Giardiasis) infection and intestinal cancer, This study contain 4 groups :- Group (G1) People with cancer and diarrhea due to the parasite (42) Group (G2) People with cancer and diarrhea without parasites (8) Group (G3) People with diarrhea and parasites (24) and Group (G4) Control (30), blood samples were collected from patients suffering from diarrhea and parasite infection of both types, as well as cancer, Elisa kits were used in our study the proteins (mucin 2, TFF3, CALP) level were measure by using Elisa kit that provided from the China Origin Company Elabscience. The results of the current immunological study showed the level of serum (mucin 2, TFF3, CALP) among the study groups, where the levels of mucin 2 values were (14305.00), (10595.00),(13145.00) and (9350.00)in group (1), and group (2), group (3) and group (4) respectively, and the level of serum values (TFF3)(43.15),(11.90),(29.65) and (8.60)with the same sequence of groups above, and the level of serum values CALP(16320.00),(11220.00),(15275.00) and(8690.00)with the same sequence of groups above as well. The results of the statistical analysis showed that there is a significant difference between the study groups below the probability level (P<0.001). (mucin 2, TFF3, CALP) with both (carcinogenic parasite) and (parasitic infestation only) and (carcinogenic infection) with different high levels compared to other groups. Our study was concluded there was relationship between E. histolytic and Giardia lamblia infection and intestinal cancer .